2022
DOI: 10.3991/ijet.v17i17.34173
|View full text |Cite
|
Sign up to set email alerts
|

On the Entrepreneurial Intention and Entrepreneurial Behavior Path of College Students Based on the Theory of Planned Behavior

Abstract: It is of practical significance to explore the mechanism of entrepreneurship education on college students’ entrepreneurial intention, as it can provide reference for the innovations in college students’ entrepreneurial ability training mode and the formulation of relevant supporting policies. At present, the relevant research on the influence mechanism of entrepreneurship education on college students’ entrepreneurial intention is not deep enough and lacks relevant empirical analysis, which has led to great d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Finally, regarding cultural factors, it was found that having the idea of entrepreneurship and the sector where one wants to undertake indicate a significant association with the entrepreneurial behavior of university students. The results obtained are strengthened by the findings of Espinoza et al, 2019;Zhao, 2022, Aliedan et al, 2022 determined that there is a high intentionality index and that it is strongly explained by the attitude towards the behavior and by the self-efficacy in university students.…”
Section: Discussionmentioning
confidence: 78%
“…Finally, regarding cultural factors, it was found that having the idea of entrepreneurship and the sector where one wants to undertake indicate a significant association with the entrepreneurial behavior of university students. The results obtained are strengthened by the findings of Espinoza et al, 2019;Zhao, 2022, Aliedan et al, 2022 determined that there is a high intentionality index and that it is strongly explained by the attitude towards the behavior and by the self-efficacy in university students.…”
Section: Discussionmentioning
confidence: 78%
“…In the past two decades, the theory of planned behavior (TPB) has been increasingly utilized by scholars, either in its entirety or by incorporating its elements, to elucidate the development of entrepreneurial intention (Adu et al, 2020;Bičo & Knezović, 2023;Chhabra et al, 2020;Debarliev et al, 2015;Fayolle et al, 2006;Ferreira et al, 2012;Guzmán-Alfonso & Guzmán-Cuevas, 2012;Hejazinia, 2015;Henley et al, 2017;Iakovleva et al, 2011;Moi et al, 2011;Munir et al, 2019;Suryawirawan, 2020;Yang, 2013;Zhao, 2022). This study will incorporate attitudes, subjective norms, behavioral control, and exogenous SDG variables.…”
Section: Introductionmentioning
confidence: 99%